PENGARUH AKTIVITAS FISIK INDEKS MASSA TUBUH DAN KUALITAS TIDUR TERHADAP KEBUGARAN JASMANI SISWA KELAS XI DI SMK-SMTI MAKASSAR - Ihsan, Andi; Nawir, Nukhrawi; Hasyim, Hasyim; Hudain, Muh. Adnan; Fauzan, M (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2024)
The purpose of this study was to determine the direct effect of physical activity, body mass index, sleep quality on the physical fitness of Class XI students of SMK-SMTI Makassar. This type of research includes quantitative research with simple linear regression analysis. The population of this study included all Class XI students of SMK-SMTI Makassar totaling 224 people with a sample size of 30 people, namely 15 men 15 women. The results showed that (1) There is a positive effect of physical activity on physical fitness in class XI students of SMTI Makassar, (2) There is a significant negative effect of body mass index on physical fitness in class XI students of SMTI Makassar, (3) There is an insignificant positive effect of sleep quality on physical fitness in class XI students of SMTI Makassar, (4) The effect of physical activity, body mass index and sleep quality on physical fitness variables in class XI students of SMTI Makassar is 44.2%. The remaining percentage of 55.8% is influenced by other factors.